Myocardial motion and deformation patterns in an experimental swine model of acute LBBB/CRT and chronic infarct - Duchateau, Nicolas; Sitges, Marta; Doltra, Adelina; Fernández-Armenta, Juan; Solanes, Nuria; Rigol, Montserrat; Gabrielli, Luigi; Silva, Etelvino; Barceló, Aina; Berruezo, Antonio; Mont, Lluís; Brugada, Josep; et al. (International Journal of Cardiovascular Imaging, 2014)
In cardiac resynchronization therapy (CRT), specific changes in motion/deformation happen with left-bundle-branch-block (LBBB) and following treatment. However, they remain sub-optimally studied. We propose a two-fold improvement of their characterization. This includes controlling them through an experimental model and using more suitable quantification techniques. We used a swine model of acute LBBB and CRT with/without chronic infarct (pure-LBBB: N = 11; LBBB + left-anterior-descending infarct: N = 11). Myocardial displacement, velocity and strain were extracted from short-axis echocardiographic sequences using 2D speckle-tracking. The data was transformed to a single spatiotemporal system of coordinates to perform subject comparisons and quantify pattern changes at similar locations and instants. Pure-LBBB animals showed a specific intra-ventricular dyssynchrony pattern with LBBB (11/11 animals), and the recovery towards a normal pattern with CRT (10/11 animals). Pattern variability was low within the pure-LBBB population, as quantified by our method. This was not correctly assessed by more conventional measurements. Infarct presence affected the pattern distribution and CRT efficiency (improvements in 6/11 animals). Pattern changes correlated with global cardiac function (global circumferential strain) changes in all the animals (corrected: p LBBBvsBaseline < 0.001, p CRTvsBaseline = NS; non-corrected: p LBBBvsBaseline = NS, p CRTvsBaseline = 0.028). Our LBBB/CRT experimental model allowed controlling specific factors responsible for changes in mechanical dyssynchrony and therapy. We illustrated the importance of our quantification method to study these changes and their variability. Our findings confirm the importance of myocardial viability and of specific LBBB-related mechanical dyssynchrony patterns.